Evolution of the E-Commerce Ecosystem and Its Impact on Business Models (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The digital transformation of commerce has reshaped e-commerce from a transaction-oriented channel into a complex, platform-mediated ecosystem involving multiple interdependent actors. This study positions itself as a conceptual and narrative review that critically examines the evolution of the e-commerce ecosystem and its implications for contemporary business models. Drawing on recent peer-reviewed literature, policy reports, and conceptual frameworks, the paper analyses how platform governance, ecosystem power asymmetries, data control, and network effects influence value creation and strategic decision-making. The review highlights a structural transition from linear value chains to ecosystem-based business models while critically addressing risks related to platform dominance, strategic dependency, and long-term sustainability. The study contributes theoretically by integrating ecosystem and platform perspectives into business model analysis and offers informed implications for firms and policymakers.